Glass fiber reinforced nylon material with low linear expansion coefficient and preparation method
By using glass fiber, nylon resin, acrylamide-1-ethyl-3-methylimidazole ethyl sulfate random copolymer and bisphenol A type epoxy resin in nylon materials, combined with modified carbonization Polyimide composites and S-EED and acetylanilide absorbers solve the curing rate, chemical properties and cost problems of glass fiber reinforced nylon materials with low linear expansion coefficient, and achieve efficient preparation and environmental protection of the material.
Patent Information
- Application Number
- CN202411295289.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-17
- Publication Date
- 2024-12-20
AI Technical Summary
The existing technology cannot effectively realize the high curing rate, strengthening performance, photoanti-aging protection, low cost and strong capability of glass fiber reinforced nylon materials with low linear expansion coefficient, resulting in large changes in size and shape of the material when temperature changes. Distortion and size mismatch, great potential environmental impact, difficulty in handling and recycling of waste materials, and enhanced high glass fiber content leads to poor dimensional stability and poor surface of the material.
20 to 45 parts of glass fiber, 20 to 60 parts of nylon resin and 15 to 30 parts of acrylamide-1-ethyl-3-methylimidazole ethyl sulfate random copolymer as toughening agent, combined with 16 to 16 to 30 parts of 24 parts of bisphenol A type epoxy resin and zirconium diboride, prepared glass fiber reinforced nylon material by modifying the carbide polyimide composite, S-EED and acetylanilide absorber UVA-1 composition. , prepared by high-temperature carbonization reaction, pressurization, heating curing reaction and in-situ radical solution polymerization.
It achieves enhanced tensile strength, bending strength and impact toughness, good specific strength and specific stiffness, excellent electrical insulation performance and heat resistance insulation performance, reduces raw material costs, improves the curing rate and manufacturability of the material, and reduces the Difficulty in handling waste materials.
Smart Images

Figure CN119161726A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer composite materials, in particular to a low linear expansion coefficient glass fiber reinforced nylon material and a preparation method thereof. Background Art
[0002] Glass fiber is a commonly used reinforcement material. Its high strength and stiffness can significantly improve the mechanical properties of matrix materials such as nylon. By adding an appropriate amount of glass fiber to the nylon matrix, the mechanical properties and heat resistance of the material can be significantly improved. Compared with traditional nylon materials, glass fiber reinforced nylon materials have a lower linear expansion coefficient, which means that the material's dimensions change less when the temperature changes, reducing the risk of shape distortion and size mismatch.
[0003] However, the cost of glass fiber reinforced nylon is relatively high, the preparation process is relatively complicated, special processing equipment and technology are required, there are some potential impacts on the environment, and the treatment and recycling of waste materials are extremely difficult. High glass fiber content reinforcement can lead to problems such as poor dimensional stability and poor surface.
[0004] Patent document CN105504798B discloses a glass fiber reinforced nylon composite material. The above patent achieves synergistic reinforcement through nano-layered silicate filler and glass fiber, which not only maintains the advantages of glass fiber reinforced nylon composite materials, but also further improves the strength and toughness of the composite material, overcomes the shortcomings of poor material dimensional stability and poor surface caused by high glass fiber content reinforcement, and has little effect on the color of the material. It has excellent mechanical properties and good fluidity, and can be used in the manufacture of machinery and automotive parts that require high strength. However, the above patent cannot achieve a high curing rate when preparing glass fiber reinforced nylon materials with low linear expansion coefficients.
[0005] Patent document CN110628131B discloses a low shrinkage, low linear expansion coefficient polypropylene composite material and a preparation method. The above patent achieves that by using special filler A to replace traditional talcum powder to fill polypropylene, the shrinkage rate and CLTE can be significantly reduced without increasing the weight. However, the above patent cannot achieve the strong chemical properties of glass fiber reinforced nylon materials.
[0006] Patent document CN113248913B discloses a glass fiber reinforced nylon composite material and a preparation method thereof. The above patent realizes the addition of modified glass fiber to nylon 66, so that the prepared composite material has higher mechanical properties and heat deformation temperature, but the above patent cannot provide light anti-aging protection for glass fiber reinforced nylon materials.
[0007] Patent document CN103436008B discloses an ultra-high glass fiber reinforced nylon material and a preparation method thereof. The above patent achieves high specific strength of the ultra-high glass fiber reinforced nylon material, no obvious floating fibers on the surface, high wet retention rate of tensile properties and bending properties, good product dimensional stability, and improved rigidity retention rate of the material in a wet environment, which greatly broadens the scope of use of the material. However, the above patent cannot achieve low cost and strong manufacturability of low linear expansion coefficient glass fiber reinforced nylon materials.
[0008] In summary, the above patents cannot achieve the high curing rate when preparing low linear expansion coefficient glass fiber reinforced nylon materials, the strong chemical properties of glass fiber reinforced nylon materials, the light anti-aging protection provided to glass fiber reinforced nylon materials, the low cost and strong manufacturability of low linear expansion coefficient glass fiber reinforced nylon materials, resulting in small changes in the size of the material when the temperature changes, reducing shape distortion and size mismatch, and there are some potential impacts on the environment. The treatment and recycling of waste materials are extremely difficult. High glass fiber content reinforcement will lead to poor dimensional stability and poor surface of the material. To this end, the present application proposes a low linear expansion coefficient glass fiber reinforced nylon material and a preparation method that can achieve a high curing rate during the preparation of the low linear expansion coefficient glass fiber reinforced nylon material, strong chemical properties of the glass fiber reinforced nylon material, provide light anti-aging protection for the glass fiber reinforced nylon material, low cost and strong manufacturability of the low linear expansion coefficient glass fiber reinforced nylon material. Summary of the invention
[0009] The purpose of the present invention is to provide a low linear expansion coefficient glass fiber reinforced nylon material and a preparation method to solve the problems proposed in the above background technology that the high curing rate during the preparation of the low linear expansion coefficient glass fiber reinforced nylon material, the strong chemical properties of the glass fiber reinforced nylon material, the light anti-aging protection provided to the glass fiber reinforced nylon material, the low cost and strong manufacturability of the low linear expansion coefficient glass fiber reinforced nylon material can not be achieved. A low linear expansion coefficient glass fiber reinforced nylon material and a preparation method, resulting in a smaller size change of the material when the temperature changes, reducing shape distortion and size mismatch, there are some potential impacts on the environment, and the treatment and recycling of waste materials are extremely difficult. The high glass fiber content reinforcement will lead to poor dimensional stability and poor surface of the material.
[0010] To achieve the above object, the present invention provides the following technical solution: a low linear expansion coefficient glass fiber reinforced nylon material, the low linear expansion coefficient glass fiber reinforced nylon material comprising the following components in parts by weight: 20 to 45 parts of glass fiber, 20 to 60 parts of synthetic polymer and 15 to 30 parts of additive A, the synthetic polymer is nylon resin; The additive A is a toughening agent, and the toughening agent is acrylamide-acrylic acid-1-ethyl-3-methylimidazolium ethyl sulfate random copolymer.
[0011] Preferably, the 15-30 parts of acrylamide-acrylic acid-1-ethyl-3-methylimidazolium ethyl sulfate random copolymer is a random copolymer of 5-6 parts of acrylamide and 5-6 parts of acrylic acid monomer polymer reacted with 5-6 parts of 1-ethyl-3-methylimidazolium ethyl sulfate.
[0012] Preferably, the glass fiber reinforced nylon material further includes 16 to 24 parts of additive B, and additive B is bisphenol A type epoxy resin and zirconium diboride.
[0013] Preferably, the tensile strength of the toughening agent is 70-90 MPa, and the testing standards are ISO 527 and ASTM D638.
[0014] Preferably, the 16 to 24 parts of additive B include 6 to 10 parts of bisphenol A epoxy resin and 10 to 14 parts of zirconium diboride.
[0015] Preferably, the low linear expansion coefficient glass fiber reinforced nylon material further comprises the following ingredients in different amounts: 0.1 to 0.5 parts of a stabilizer, 0.05 to 0.2 parts of a catalyst and 0.1 to 0.5 parts of an antioxidant.
[0016] Preferably, the stabilizer is a combination of S-EED and acetanilide absorber UVA-1, the catalyst is an alkali metal catalyst, and the antioxidant is a hindered phenolic and / or phosphorus antioxidant; 0.1-0.5 parts of S-EED and acetanilide UVA-1 absorber The composition contains 0.05-0.2 parts of S-EED and 0.05-0.3 parts of acetanilide UVA-1 absorber.
[0017] Preferably, the nylon resin is a modified carbonized polyimide composite, and when the modified carbonized polyimide composite is used at 1000-2300° C., the strength increases with increasing temperature; 20 to 60 parts of the modified carbonized polyimide composite comprises 15 to 35 parts of graphite and 5 to 25 parts of polyimide.
[0018] Preferably, the method for preparing the low linear expansion coefficient glass fiber reinforced nylon material comprises the following steps: (1) Preparation of modified carbonized polyimide composites; Firstly, graphite powder and polyimide were weighed in a mass ratio of 1:1, magnetically stirred for 5 hours, and the mixture was subjected to vacuum carbonization reaction in a high-temperature reactor; The preform is then placed in a hot press for pressurization, heating and curing reaction; Finally, a modified carbonized polyimide composite is formed; (2) preparing acrylamide-acrylic acid-1-ethyl-3-methylimidazolium ethyl sulfate random copolymer; First, 20 parts of 1-ethyl-3-methylimidazole were added to a dry and impurity-free reaction vessel, and then vinyl ethyl sulfate was added, and the reaction mixture was stirred; After the reaction is completed, the reaction mixture is passed through a centrifuge to separate the suspended matter; The obtained liquid product is then washed with anhydrous ethanol; Finally, the washed product is purified by distillation to obtain pure 1-ethyl-3-methylimidazolium ethyl sulfate; Weigh 20 parts of acrylamide and acrylic acid, add them into deionized water, and stir magnetically for 10 minutes until they are completely dissolved; Then, by in-situ free radical solution polymerization, solvent acetone and 1-ethyl-3-methylimidazolium ethyl sulfate are added; Finally, the acetone vapor is blown out by heating and distillation to obtain a pure acrylamide-acrylic acid-1-ethyl-3-methylimidazolium ethyl sulfate random copolymer; (3) Preparation of bisphenol A epoxy resin; First, 12 g of bisphenol A and 14 g of epichlorohydrin were added in sequence into a 250 mL three-necked flask equipped with a stirrer, a dropping funnel and a thermometer, and an epoxidant was added to initiate the ring-opening reaction of the epoxy group in bisphenol A to form an epoxidized resin chain; Adding a sulfonating agent to catalyze the reaction between the epoxy group and the sulfonate group in the sulfonating agent to form a cross-linked structure; Heat in a water bath and start the stirrer to completely dissolve bisphenol A for about 0.5 h; Then, impurities on the resin surface are removed by using an ultrasonic cleaner and an appropriate amount of detergent; The washed resin is passed through a filter membrane for solid-liquid separation; Finally, the resin is purified by infrared irradiation; (4) Preparation of acetanilide absorber UVA-1; First, in a reaction container, aniline is dissolved in ether to form an ether solution of aniline; Potassium carbonate is then added to keep the reaction solution alkaline, and the temperature of the reaction solution is maintained at 0-5° C. Acetyl chloride is added dropwise to the reaction solution, and then the reaction solution is stirred, and acetyl chloride reacts with aniline to generate acetanilide; After the reaction is completed, the reaction solution is filtered, and the filtrate is washed with methanol to remove impurities; Finally, the washed product is distilled to obtain pure acetanilide absorber UVA-1; (5) preparing a composition of S-EED and acetanilide absorber UVA-1; First, add 10 parts of S-EED into a dry, anhydrous, impurity-free reaction vessel; Then add acetanilide absorber UVA-1 according to the 2:3 ratio; The two components are then uniformly dispersed by high-speed magnetic stirring, and the mixture is filtered to remove impurities; Finally, the prepared S-EED and UVA-1 composition is transferred to a dry, water-free sealed container and stored in a sealed container at 5-35°C.
[0019] Preferably, the preparation method further comprises the following steps: (1) hot-melt mixing the glass fiber, catalyst, antioxidant, zirconium diboride and the above-mentioned 9 materials in a high-speed mixer for 30 to 60 minutes, wherein the speed of the high-speed mixer is 3000 rpm; (2) placing the mixed materials in step (1) into a melting machine and melting the mixture at high temperature to make it a fluid state; The molten material is then pressed into shape by a punch; Then solidify by cooling; Finally, the cured material is subjected to subsequent treatment to obtain a glass fiber reinforced nylon material with a low linear expansion coefficient; The temperature of the melting machine changes from the beginning to the end at 80°C, 180°C, -40°C, 190°C, 210°C, and 240°C. Gas cooling is used for cooling, and rapid solidification is required.
[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention achieves enhanced tensile strength, flexural strength and impact toughness, good specific strength and specific stiffness, excellent electrical insulation performance and heat-resistant insulation performance by preparing a modified carbonized polyimide composite, thereby solving the problem that the material cannot be used and is easy to break under extreme temperature conditions and cannot be insulated and heat-insulated; 2. The present invention achieves the provision of light anti-aging protection for low linear expansion coefficient glass fiber reinforced nylon materials by preparing acrylamide-acrylic acid-1-ethyl-3-methylimidazolium ethyl sulfate random copolymers, thereby solving the problem of color change and loss of support of low linear expansion coefficient glass fiber reinforced nylon materials due to long-term light exposure; 3. The present invention reduces the usage rate of traditional nylon by preparing bisphenol A epoxy resin, and solves the problem that the glass fiber reinforcement and high-grade nylon resin in the raw materials are relatively expensive, which increases the manufacturing cost; 4. The present invention achieves a high curing rate of raw material preparation by preparing a composition of S-EED and acetanilide absorber UVA-1, solves the problem that the raw materials are relatively complicated during the processing and a large amount of waste cannot be recycled, improves the utilization rate of raw materials, and reduces energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The present invention is a flow chart for preparing acrylamide-acrylic acid-1-ethyl-3-methylimidazolium ethyl sulfate random copolymer; Figure 2 It is a preparation flow chart of bisphenol A epoxy resin; Figure 3 is a flow chart for the preparation of a composition of S-EED and UVA-1; Figure 4 The present invention is a flow chart for the preparation of modified carbonized polyimide composites; Figure 5 This is a flow chart for the preparation of low linear expansion coefficient glass fiber reinforced nylon materials. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] See also Figure 1 , an embodiment provided by the present invention: a low linear expansion coefficient glass fiber reinforced nylon material and a preparation method, the low linear expansion coefficient glass fiber reinforced nylon material comprises the following components in parts by weight: 20 to 45 parts of glass fiber, 20 to 60 parts of synthetic polymer and 15 to 30 parts of additive A, the synthetic polymer is nylon resin; The additive A is a toughening agent, which is a random copolymer of acrylamide-acrylic acid-1-ethyl-3-methylimidazolium ethyl sulfate; the random copolymer of 15 to 30 parts of acrylamide-acrylic acid-1-ethyl-3-methylimidazolium ethyl sulfate is a random copolymer of 5 to 6 parts of acrylamide and 5 to 6 parts of acrylic acid monomers reacted with 5 to 6 parts of 1-ethyl-3-methylimidazolium ethyl sulfate, the tensile strength of the toughening agent is 70 to 90 MPa, and the testing standards are ISO 527 and ASTMD638; Further, first, 20 parts of 1-ethyl-3-methylimidazole are added to a dry and impurity-free reaction container, vinyl ethyl sulfate is slowly added to the reaction container at room temperature, and the reaction mixture is stirred, the reaction temperature is kept low and carried out at room temperature, and the reaction mixture is continuously stirred for a time range of several hours to tens of hours. Next, after the reaction is completed, the reaction mixture is separated from suspended matter by a centrifuge, and then the obtained liquid product is washed with anhydrous ethanol, and finally, the washed product is purified by distillation to obtain pure 1-ethyl-3-methylimidazole ethyl sulfate; Weigh 25 parts of acrylamide and acrylic acid, add them into deionized water, stir magnetically for 10 minutes until they are completely dissolved, add solvent acetone and 1-ethyl-3-methylimidazolium ethyl sulfate through in-situ free radical solution polymerization, finally blow out acetone vapor through heating distillation, collect the solvent through a reflux condenser for recycling, and obtain a pure acrylamide-acrylic acid-1-ethyl-3-methylimidazolium ethyl sulfate random copolymer.
[0024] See also Figure 2 , an embodiment provided by the present invention: a glass fiber reinforced nylon material with a low linear expansion coefficient and a preparation method thereof, wherein the glass fiber reinforced nylon material further comprises 16 to 24 parts of additive B, wherein additive B is bisphenol A type epoxy resin and zirconium diboride; Furthermore, first, 12 grams of bisphenol A and 14 grams of epichlorohydrin are added in sequence into a 250 mL three-necked flask equipped with a stirrer, a dropping funnel and a thermometer, and an epoxidant is added to initiate a ring-opening reaction of the epoxy groups in the bisphenol A to form an epoxidized resin chain, and the alkylating agent catalyzes the reaction of the epoxy groups with the alkylating agents in the alkylating agent to form a cross-linked structure, and the mixture is heated in a water bath and the stirrer is started to completely dissolve the bisphenol A for about 0.5 hours, and then impurities on the resin surface are removed by an ultrasonic cleaner and an appropriate amount of detergent, the washed resin is passed through a filter membrane for solid-liquid separation, and finally the resin is purified by infrared irradiation.
[0025] See also Figure 3 , an embodiment provided by the present invention: a low linear expansion coefficient glass fiber reinforced nylon material and a preparation method, the low linear expansion coefficient glass fiber reinforced nylon material also includes the following components in different amounts: 0.1 to 0.5 parts of a stabilizer, 0.05 to 0.2 parts of a catalyst and 0.1 to 0.5 parts of an antioxidant; The stabilizer is a combination of S-EED and acetanilide absorber UVA-1, the catalyst is an alkali metal catalyst, and the antioxidant is a hindered phenolic and / or phosphorus antioxidant; The 0.1-0.5 parts S-EED and acetanilide absorber UVA-1 composition comprises 0.05-0.2 parts S-EED and 0.05-0.3 parts acetanilide absorber UVA-1; Further, firstly, in a reaction container, aniline is dissolved in ether to form an ether solution of aniline, potassium carbonate is added to keep the reaction solution alkaline, the temperature of the reaction solution is kept at 0-5°C, acetyl chloride is added dropwise to the reaction solution, and then the reaction solution is stirred, acetyl chloride reacts with aniline to form acetanilide, stirring is continued for several hours to tens of hours to fully complete the reaction, after the reaction is completed, the reaction solution is filtered, the filtrate is washed with methanol to remove impurities, and finally, the washed product is distilled to obtain a pure acetanilide absorber UVA-1; Then, 10 parts of S-EED are added to a dry, anhydrous, impurity-free reaction container, and then acetanilide absorber UVA-1 is added according to a 2:3 ratio, and then high-speed magnetic stirring is performed until the two components are evenly dispersed, and then the mixture is filtered to remove impurities, and finally the prepared S-EED and UVA-1 composition is transferred to a dry, anhydrous sealed container, and stored in a sealed container at 5 to 35°C.
[0026] See also Figure 4 , an embodiment provided by the present invention: a glass fiber reinforced nylon material with a low linear expansion coefficient and a preparation method thereof, wherein the nylon resin is a modified carbonized polyimide composite, and when the modified carbonized polyimide composite is used at 1000-2300°C, the strength increases with increasing temperature; 20 to 60 parts of the modified carbonized polyimide composite comprises 15 to 35 parts of graphite and 5 to 25 parts of polyimide; Furthermore, graphite powder and polyimide are first weighed in a mass ratio of 1:1, and magnetically stirred for 5 hours. The mixture is placed in a high-temperature reactor at 800-900°C for vacuum carbonization reaction, and then the preform is placed in a hot press for pressurization and heating curing reaction to finally form a composite material.
[0027] See also Figures 1 to 5 , an embodiment provided by the present invention: a glass fiber reinforced nylon material with low linear expansion coefficient and a preparation method thereof, the preparation method further comprising the following steps, The glass fiber, catalyst, antioxidant, zirconium diboride and the raw materials prepared in Examples 1 to 4 are melt-mixed in a high-speed mixer for 30 to 60 minutes to uniformly disperse the raw materials, wherein the speed of the high-speed mixer is 3000 rpm; Further, the mixed material is placed in a melting machine for melting processing. During the processing, the mixture is melted at high temperature to become a fluid state, and then the molten material is pressed into shape by a punching machine; After the melt processing, the material enters the cooling area, where it is rapidly solidified by cooling. The cooling method uses gas cooling, and rapid solidification is required. Finally, the cured material is subjected to subsequent processing, such as cutting, molding, surface treatment, etc., to obtain the glass fiber reinforced nylon material with low linear expansion coefficient required for the application; The temperature of the melting machine changes from the beginning to the end as 80°C, 180°C, -40°C, 190°C, 210°C, and 240°C.
[0028] See also Figures 1 to 5, an embodiment provided by the present invention: a low linear expansion coefficient glass fiber reinforced nylon material and a preparation method, the low linear expansion coefficient glass fiber reinforced nylon material comprising the following components in parts by weight: 20 to 45 parts of glass fiber, 20 to 60 parts of modified carbonized polyimide composite and 15 to 30 parts of acrylamide-acrylic acid-1-ethyl-3-methylimidazolium ethyl sulfate random copolymer, 0.1 to 0.5 parts of S-EED and acetanilide absorber UVA-1 composition, 16 to 24 parts of additive B, 0.1 parts of catalyst and 0.02 parts of antioxidant; Further, a control group 1 and experimental groups 1 to 4 were set up, and the preparation process was all based on Example 5. The control group 1 used ordinary nylon resin and chopped glass fiber reinforcement, 0.1 part of catalyst and 0.02 part of antioxidant; the experimental group 1 used 20 parts of glass fiber, 20 parts of modified carbonized polyimide composite and 15 parts of acrylamide-acrylic acid-1-ethyl-3-methylimidazol ethyl sulfate random copolymer, 0.1S-EED and acetanilide absorber UVA-1 composition, 16 parts of additive B, 0.1 part of catalyst and 0.02 part of antioxidant; the experimental group 2 used an ordinary toughening agent instead of acrylamide-acrylic acid-1-ethyl-3-methylimidazol ethyl sulfate random copolymer, and the rest was the same as the experimental group 1; the experimental group 3 did not add the S-EED and acetanilide absorber UVA-1 composition; the experimental group 4 did not add additive B; the low linear expansion coefficient glass fiber reinforced nylon materials obtained in the control group 1 and experimental groups 1 to 4 were tested and analyzed, and the specific test and analysis results are shown in Table 1: Test items Control group 1 Experimental Group 1 Experimental Group 2 Experimental Group 3 Experimental Group 4 CLTE linear expansion coefficient (µm / m-°C) 358 96 111 100 124 Rigidity (N / m) 3 5.2 3.6 3.8 3.5 Tensile strength N / (MPa) 2120 2400 2150 2330 2130 Elastic modulus (Pa) 3540 3900 3630 3850 3760 Thermogravimetric analysis (TGA) generally excellent good generally generally Heat deformation temperature (℃) 265 385 320 300 284 Corrosion rate (h) 24 45 30 36 34 Working principle: first, a modified carbonized polyimide composite is prepared through high-temperature carbonization reaction, pressurization, and heating curing reaction, and then acrylamide-acrylic acid-1-ethyl-3-methylimidazolethyl sulfate random copolymer is prepared through in-situ free radical solution polymerization, and then a bisphenol A epoxy resin, S-EED and acetanilide absorber UVA-1 composition is prepared, and then glass fiber, catalyst, antioxidant, zirconium diboride and the prepared raw materials are mixed and put into a melting machine for melt processing through high-temperature melting to make the mixture into a fluid state, and then the molten material is pressed into shape by a punching machine, and the material after melt processing enters the cooling area, and the material is rapidly solidified by gas cooling, and finally the solidified material is subjected to subsequent treatment.
[0029] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and range of equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A glass fiber reinforced nylon material with low linear expansion coefficient, characterized in that: The low linear expansion coefficient glass fiber reinforced nylon material comprises the following components in parts by weight: 20 to 45 parts of glass fiber, 20 to 60 parts of synthetic polymer and 15 to 30 parts of additive A, wherein the synthetic polymer is nylon resin; The additive A is a toughening agent, and the toughening agent is acrylamide-acrylic acid-1-ethyl-3-methylimidazolium ethyl sulfate random copolymer.
2. The low linear expansion coefficient glass fiber reinforced nylon material according to claim 1, characterized in that: The 15-30 parts acrylamide-acrylic acid-1-ethyl-3-methylimidazolium ethyl sulfate random copolymer is a random copolymer obtained by reacting 5-6 parts of acrylamide and 5-6 parts of acrylic acid monomer polymer with 5-6 parts of 1-ethyl-3-methylimidazolium ethyl sulfate.
3. The low linear expansion coefficient glass fiber reinforced nylon material according to claim 1, characterized in that: The glass fiber reinforced nylon material also includes 16 to 24 parts of additive B, and additive B is bisphenol A type epoxy resin and zirconium diboride.
4. The low linear expansion coefficient glass fiber reinforced nylon material according to claim 1, characterized in that: The tensile strength of the toughening agent is 70-90 MPa, and the testing standards are ISO 527 and ASTM D638.
5. The low linear expansion coefficient glass fiber reinforced nylon material according to claim 3, characterized in that: The 16-24 parts of additive B include 6-10 parts of bisphenol A epoxy resin and 10-14 parts of zirconium diboride.
6. The low linear expansion coefficient glass fiber reinforced nylon material according to claim 1, characterized in that: The low linear expansion coefficient glass fiber reinforced nylon material also includes the following ingredients in different amounts: 0.1 to 0.5 parts of a stabilizer, 0.05 to 0.2 parts of a catalyst and 0.1 to 0.5 parts of an antioxidant.
7. The low linear expansion coefficient glass fiber reinforced nylon material according to claim 6, characterized in that: The stabilizer is a combination of S-EED and acetanilide absorber UVA-1, the catalyst is an alkali metal catalyst, and the antioxidant is a hindered phenolic and / or phosphorus antioxidant; 0.1-0.5 parts of S-EED and acetanilide UVA-1 absorber The composition contains 0.05-0.2 parts of S-EED and 0.05-0.3 parts of acetanilide UVA-1 absorber.
8. The low linear expansion coefficient glass fiber reinforced nylon material according to claim 1, characterized in that: The nylon resin is a modified carbonized polyimide composite. When the modified carbonized polyimide composite is used at 1000-2300°C, the strength increases with the increase of temperature. 20 to 60 parts of the modified carbonized polyimide composite comprises 15 to 35 parts of graphite and 5 to 25 parts of polyimide.
9. A method for preparing a glass fiber reinforced nylon material with a low linear expansion coefficient, applicable to a glass fiber reinforced nylon material with a low linear expansion coefficient as described in any one of 1 to 8, characterized in that: The preparation method comprises the following steps: (1) Preparation of modified carbonized polyimide composites; First, graphite powder and polyimide were weighed in a mass ratio of 1:1, magnetically stirred for 5 hours, and the mixture was vacuum carbonized in a high-temperature reactor. Then the preform is placed in a hot press for pressurization, heating and curing reaction. Finally, a modified carbonized polyimide composite is formed; (2) preparing acrylamide-acrylic acid-1-ethyl-3-methylimidazolium ethyl sulfate random copolymer; First, add 20 parts of 1-ethyl-3-methylimidazole into a dry and impurity-free reaction vessel, then add vinyl ethyl sulfate, and stir the reaction mixture. After the reaction is completed, the reaction mixture is centrifuged to separate the suspended solids. The obtained liquid product is then washed with anhydrous ethanol Finally, the washed product is purified by distillation to obtain pure 1-ethyl-3-methylimidazolium ethyl sulfate; Weigh 25 parts of acrylamide and acrylic acid, add them into deionized water, and stir magnetically for 10 minutes until they are completely dissolved. Then, by in-situ free radical solution polymerization, solvent acetone and 1-ethyl-3-methylimidazolium ethyl sulfate were added. Finally, the acetone vapor is blown out by heating and distillation to obtain a pure acrylamide-acrylic acid-1-ethyl-3-methylimidazolium ethyl sulfate random copolymer; (3) Preparation of bisphenol A epoxy resin; First, 12 g of bisphenol A and 14 g of epichlorohydrin were added into a 250 mL three-necked flask equipped with a stirrer, a dropping funnel and a thermometer, and an epoxidant was added to initiate the ring-opening reaction of the epoxy group in bisphenol A to form an epoxidized resin chain. Adding a sulfonating agent catalyzes the reaction between the epoxy group and the sulfonate group in the sulfonating agent to form a cross-linked structure Heat in a water bath and start the stirrer to completely dissolve bisphenol A for about 0.5 h. Then use an ultrasonic cleaner and an appropriate amount of detergent to remove impurities on the resin surface. The washed resin is filtered through a membrane for solid-liquid separation Finally, the resin is purified by infrared irradiation; (4) Preparation of acetanilide absorber UVA-1; First, in a reaction vessel, aniline is dissolved in ether to form an ether solution of aniline. Potassium carbonate is then added to keep the reaction solution alkaline, and the temperature of the reaction solution is maintained at 0-5°C. Acetyl chloride is added dropwise to the reaction solution, and then the reaction solution is stirred. Acetyl chloride reacts with aniline to generate acetanilide. After the reaction is completed, the reaction solution is filtered and the filtrate is washed with methanol to remove impurities. Finally, the washed product is distilled to obtain pure acetanilide absorber UVA-1; (5) preparing a composition of S-EED and acetanilide absorber UVA-1; First, add 10 parts of S-EED into a dry, anhydrous, impurity-free reaction vessel. Then add acetanilide absorber UVA-1 according to the 2:3 ratio Then use high-speed magnetic stirring to evenly disperse the two components, and then filter the mixture to remove impurities. Finally, the prepared S-EED and UVA-1 composition is transferred to a dry, water-free sealed container and stored in a sealed container at 5-35°C.
10. The method for preparing a glass fiber reinforced nylon material with a low linear expansion coefficient according to claim 9, characterized in that: The preparation method further comprises the following steps: (6) hot-melt mixing the glass fiber, catalyst, antioxidant, zirconium diboride and the above-mentioned material 9 in a high-speed mixer for 30 to 60 minutes, wherein the speed of the high-speed mixer is 3000 rpm; (7) Put the mixed materials in step (6) into a melting machine and melt them at high temperature to make the mixture into a fluid state. The molten material is then pressed into shape by a punch Then solidify by cooling Finally, the cured material is post-processed to obtain a glass fiber reinforced nylon material with a low linear expansion coefficient. The temperature of the melting machine changes from the beginning to the end at 80°C, 180°C, -40°C, 190°C, 210°C, and 240°C. Gas cooling is used for cooling, and rapid solidification is required.
Citation Information
Cited By
Carbon nano polymer material for repairing gearbox body in wind power industry as well as preparation method and rapid repairing method of carbon nano polymer material
CN122302679A
